IMPROVING READING COMPREHENSION OF GRADE VIII STUDENTS AT SMP NEGERI 2 PALU THROUGH SQ3R - Kamagi, Anastasia Fritzka; M. Said, Mawardin; Hasyim, Zarkiani; Darmawan, Darmawan (Tadulako University, 2025)
The objective of this research is to find out whether the use of the SQ3R method can improve the reading comprehension of grade VIII students at SMP Negeri 2 Palu or not. This research used a quasi-experimental research design. The sample of the research was 21 students from class VIII A as the control class and 20 students from class VIII B as the experimental one. The instruments used in this research were test, pre test, and post test. The result of the data analyzed showed that there was a significant difference between the results of the pre test and post test. The mean score of the pretest of the experimental class was 49.99 while the control one was 52.54 after giving the treatment. The mean score of the experimental class in the post test was 79.50 and the control one was 67.13. By applying 0.05 level of significance, the researcher found that the value of the t-counted (3.91) was higher than the t-table (2.0399). It means that the use of the SQ3R method can improve the reading comprehension of grade VIII students at SMP Negeri 2 Palu.